Profile of the directors of brazilian complementary pension fund entities from the corporate governance perspective - Silva, Cinthia Larissa Ferreira (2023)
This article aims to analyze the evolution of the profile of the minimal governance structure of EFPCs. Quantitative documentary research techniques were applied, with a sample of 280 brazilian entities, corresponding to 93.02% of the population, with data segregated into two periods: (2013-2017) and (2018-2022). The qualitative variables were analyzed by relative frequency, taking two periods in consideration, and associations between them. The results showed the presence of managers with a low level of academic education, although in the minority, and the predominance of men in these positions, especially for financial resource management and senior management. The evolution shows a reduction in the number of managers, as a possible result of the concentration of multi-sponsored entities; greater participation of women; and an increase in the influence of sponsors in the Deliberative Council and members in the Fiscal Council. The results ratify the importance of the principles and practices of corporate governance to reduce the risks of technical competence, conflicts of interest, and gender inequality.